Demand for non-life insurance: Evidence from select insurance markets in Africa - Chitiyo, Fadzai Chitiyo (Research of GSB, 2018)
The impact of insurance market activity within financial development is gaining more attention in academia, as the sector experiences growth within emerging markets. This paper aims to understand which macro-economic and social variables impact the growth or decline of the non-life insurance sector broadly across Africa, with a view to provide recommendations to drive increased penetration across the region. The study examines the explanatory factors of non-life insurance demand in Africa, using annual data from 1990 to 2013 on 28 countries. Using Fixed Effects Panel Data Regression, the study finds that: levels of income, and unemployment rates have a significant negative impact on non-life insurance demand; whilst population growth rates, and the level of private sector credit (to GDP) positively impacted non-life insurance demand. Urbanisation rates, and levels of merchandise trade had statistically insignificant effects on non-life insurance demand. Since these variables only explained about 11 % of the variation in the dependent variable, the study suggests that further research into the cultural and institutional (ie. Legal / regulatory) dynamics is required to improve our understanding of what conditions would stimulate non-life insurance demand in future.